The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ajpath.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Suppresses Vascular Endothelial Growth Factor–Induced Vascular Hyperpermeability and Inflammation in Retinopathy

Abstract: Diabetic macular edema (DME) is caused by blood-retinal barrier breakdown associated with retinal vascular hyperpermeability and inflammation, and it is the major cause of visual dysfunction in diabetic retinopathy. Adrenomedullin (ADM) is an endogenous peptide first identified as a strong vasodilator. ADM is expressed in the eyes and is up-regulated in various eye diseases, although the pathophysiological significance is largely unknown. We investigated the effect of ADM on DME. In Kimba mice, which overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…These results are similar to those of Imai et al , who recently found that ADM suppressed the barrier disruption induced by VEGF-A on retinal endothelial cell monolayers through effects on tight junctions. 28 In addition, we found that ADM’s effect on vascular barrier function was mediated by fortification of VE-cadherin-mediated cell-cell junctions. VE-cadherin is thought to be a master controller of endothelial integrity and regulates tight junction formation indirectly by controlling expression of component proteins claudin-5 and ZO1.…”
Section: Discussionmentioning
confidence: 83%
“…These results are similar to those of Imai et al , who recently found that ADM suppressed the barrier disruption induced by VEGF-A on retinal endothelial cell monolayers through effects on tight junctions. 28 In addition, we found that ADM’s effect on vascular barrier function was mediated by fortification of VE-cadherin-mediated cell-cell junctions. VE-cadherin is thought to be a master controller of endothelial integrity and regulates tight junction formation indirectly by controlling expression of component proteins claudin-5 and ZO1.…”
Section: Discussionmentioning
confidence: 83%
“…Isolectin B4 staining has been previously used to visualize endothelial cells in the retinal vasculature. 25 Comparing images of FITC perfusion and isolectin B4 staining in retinal flat mounts after CRVO, the distributions of FITC and isolectin B4 positivity were found to differ somewhat ( Figure 5A). In images of FITC-perfused retinas, nonperfused areas could not be clearly visualized ( Figure 5A).…”
Section: Evaluation Of Macrophages and Microglia In Retinal Flat Mountsmentioning
confidence: 98%
“…23,24 Exogenous administration of ADM suppresses vascular hyperpermeability and inflammation in a DR model. 25 These observations prompted us to investigate the relationship between ADM and CRVO.…”
mentioning
confidence: 99%
“…Severe non-proliferative DR (NPDR) is characterized by increasing retinal oedema, venous abnormalities ("beading") ( Figure 6) and deposits of lipid-rich exudates often concentrated around the macula/fovea. Both PDR and macular edema ( Figure 6a) are driven by high local levels of hypoxia and release of VEGF (110,(113)(114)(115). Sight loss from macular edema is typical of T2D while intraocular haemorrhage and tractional retinal detachment are more common in T1D, although both causes of sight loss frequently occur in either type of diabetes.…”
Section: Primary and Secondary Features Of Diabetic Retinopathymentioning
confidence: 99%